2015
DOI: 10.1093/europace/euv045
|View full text |Cite
|
Sign up to set email alerts
|

Plasma galectin-3 predicts clinical outcomes after catheter ablation in persistent atrial fibrillation patients without structural heart disease

Abstract: Plasma Gal-3 concentrations are elevated in PsAF patients without structural heart disease and independently predict AF recurrence after ablation. Plasma Gal-3 concentration may be helpful in identifying appropriate candidates for AF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 26 publications
4
44
0
3
Order By: Relevance
“…Fourteen studies compared serum concentrations of galectin‐3 between the sinus rhythm group and AF group . Our meta‐analysis shows that the AF group had higher concentrations of galectin‐3 than the sinus rhythm (SR) group (mean difference [MD] = −0.68 ng/mL, 95% CI: −0.92, −0.44, Z = 5.61, P < .00001) (Figure A).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Fourteen studies compared serum concentrations of galectin‐3 between the sinus rhythm group and AF group . Our meta‐analysis shows that the AF group had higher concentrations of galectin‐3 than the sinus rhythm (SR) group (mean difference [MD] = −0.68 ng/mL, 95% CI: −0.92, −0.44, Z = 5.61, P < .00001) (Figure A).…”
Section: Resultsmentioning
confidence: 98%
“…Among the 38 full‐text articles assessed for eligibility, ten were excluded for the following reasons: One study lacked a control group; one study population was heart failure; four studies lacked available data for further analysis; and four reported duplicate data from studies that later published as full text . Finally, 28 studies involving 10 830 patients were included in our meta‐analysis, with their baseline characteristics shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have suggested a role of increased circulating levels of Gal‐3 in predicting the severity of heart disease or a high risk of major adverse cardiovascular events (MACE) including HF (Ho et al, ; van der Velde et al, ), poor survival (Bayes‐Genis et al, ; Lok et al, ), post‐MI cardiac events (Di Tano et al, ; Grandin et al, ; Maiolino et al, ), as well as diastolic dysfunction (Wu, Li, et al, ) and severity of atrial fibrosis (Hernandez‐Romero et al, ; Takemoto et al, ; Wu, Su, et al, ). French et al reported in HF patients ( n = 1,385) that elevated Gal‐3 level was associated with a greater risk of MACE (hazard ratio = 1.96 for each doubling in Gal‐3) and that such association was most pronounced among patients diagnosed as HF with preserved ejection fraction (hazard ratio = 3.30; French et al, ).…”
Section: Gal‐3 As a Biomarker Of Heart Disease: Influence Of β‐Adrenomentioning
confidence: 99%
“…12,25,26 This study may help to explain why this is the case, as it suggests that systemic (or at least non- help to explain why it has shown more promise. In this study, however, we have shown that ICTP does not appear to be significantly associated with LA fibrosis.…”
Section: Discussionmentioning
confidence: 89%